Pemberdayaan Umkm Desa Ombul Berbasis Kearifan Lokal - Chaoirul anam; Suci Indah Sari; mohammad arief (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2022)
The most superior natural resource in the Ombul community is rice where they apply a rainfed system meaning they make rainwater the main supplier of agricultural land. Of course, this also has risks when the dry season arrives. So, the Ombul village community could not plant rice. The Ombul village community also has Ombul UMKM but the program is not running. This is due to young people who migrate looking for work out of town to make ends meet during the absence of the rainy season. There are other causes that make Ombul UMKM not run well, namely: a.) The economic conditions of the community that encourage parents to prefer their children to migrate rather than continue their education, b) The willingness or thought to produce products such as the use of bamboo trees for the community, especially Ombul UMKM is lacking. Based on the observations of previous PKM proposers in overcoming the above problems, a solution is needed. Here we invite Ombul's MSME partners to hold a program in the form of a "Digital Marketing Workshop" which will be held for 2 days, namely on Wednesday and Thursday, 16-17 February 2023. The program aims to utilize natural resources such as bamboo trees into finished goods. and increase in family income. The Community Service held in the village of Ombul Arosbaya- Bangkalan is expected that the community can think creatively and innovatively in producing a product from natural wealth and know how to market the product.